Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Flotation mechanism of an amide-based fatty acid collector for quartz ore: A gene-matching perspective - Wenda Guo; Baida Chen; Zhenyue Zhang; Sicheng Li; Han Zhang; Heng Zhang; Hanjun Wu; Defeng Liu (Minerals Engineering, 2026)

Alfalfa polysaccharides-driven Kineothrix alysoides alleviates deoxynivalenol-induced intestinal injury by regulating macrophage polarization - Shouren Li; Zhaoyang Li; Congbin Chen; Mengqi Liu; Yalei Cui; Xiaoyan Zhu; Zhichang Wang; Hao Sun; Defeng Li; Boshuai Liu; Yinghua Shi (Journal of Hazardous Materials, 2026)

Evaluation of an Automated Vaccination Strategy Against Aeromonas hydrophila in Grass Carp: A Comparative Study with Conventional Manual Injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Jian Zhao; Songming Zhu; Zhangying Ye (Fishes, 2026)
(1) Background: Vaccination is crucial for Ctenopharyngodon idella, yet the impact of delivery methods on welfare and immunity requires investigation. (2) Methods: This study compared manual (HI-V) and automated (AI-V) injections of inactivated Aeromonas hydrophila vaccine. (3) Results: Both methods induced protective immunity, with AI-V achieving a slightly higher Relative Percent Survival (41.67%) than HI-V (37.84%). AI-V promoted stable erythropoiesis and robust systemic/mucosal IgM responses with elevated HSP70 and IL-6. Conversely, HI-V triggered sharp transient stress and upregulated Gadd45γ, indicating greater genotoxic stress. (4) Conclusions: Automated injection offers comparable immune protection with reduced physiological stress and improved homeostasis, supporting its use for welfare-conscious aquaculture.

Bioaugmentation of strain Bacillus sp. hex-HIT36 towards industrial wastewater 1-Hexadecene removal in biological aerated filter reactors - Lei Yang; Yijie Liu; Yuxin Pan; Xue-Ting Wang; Wei Wang; Xijun Xu; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2026)

Rare Bacterial Taxa Drive Soil Multifunctionality in Lakeside Wetlands of Eutrophic Lake - Lingchen Yuan; Jiajia Zhang; Mengxi Gao; Renlei Yang; Yue Chen; Bin Hu; Defeng Feng; Wei Li (Wetlands, 2026)

Elastic conductive polyurethane/PEDOT:PSS composite with self-healing and closed-loop recyclability - Wei-Chen Gao; Ben Fan; Junmei Hu; Yu-Dong Zhao; Xiang Sun; Defeng Cui; Jing Qiao; Wei-Bing Lu; Ying-Shi Guan (Chemical Engineering Journal, 2025)

Physiological stress and tissue damage response of Ctenopharyngodon idella to artificial and automated injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Chenqing Zhang; Songming Zhu; Zhangying Ye (Aquaculture International, 2025)

Nutrient cycles in transition: C:N:P stoichiometry by forest conversion to plantations - Ying Wang; Anna Gunina; Peter B. Reich; Defeng Yang; Han Y.H. Chen; Yakov Kuzyakov; Yongxing Cui; Jingwen Chen; Zhiming Guo; Tao Sun (Forest Ecology and Management, 2025)

Direct ammonia oxidation colony-driven DAAO process: construction strategy and optimization of denitrification efficacy - Yuwei Mi; Dingqiu Wei; Shuangjiang Liu; Defeng Li; Han Chen; Yijie Zheng; Mingming Chen; Dongru Qiu; Renbing Bao; Jian Xu; Zhiquan Hu (Chemical Engineering Journal, 2025)

FeCN/MXene as novel heterogeneous electro-Fenton catalysts for the degradation of sulfathiazole: Performance and mechanism investigation - Huilai Liu; Zhihao Li; Defeng Kong; Xing Chen (Journal of Environmental Sciences, 2025)

Synthetic microbiome and biochar enhanced human feces aerobic mesophilic composting - Xiaoyu Cai; Jing Wang; Kun Feng; Huihui Zhou; Chuan Chen; Chuandong Wu; Rui Fang; Defeng Xing (Resources, Conservation and Recycling, 2025)

Differentiation of the Anammox core microbiome: Unraveling the evolutionary impetus of scalable gene flow - Quan Zhang; Xiao-Ming Ji; Xueting Wang; Wei Wang; Xijun Xu; Qi Zhang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Water Research, 2025)

Designing and evaluating a novel blood-brain barrier in vitro model of teleost for reproducing alterations in brain infecting - Yanghui Chen; Yi Li; Wenze Li; Yuan Li; Defeng Zhang; Yu Huang; Jia Cai; Eakapol Wangkahart; Jichang Jian; Bei Wang (Fish & Shellfish Immunology, 2025)

Applying machine learning and genetic algorithms accelerated for optimizing ethanol production - Xu Yang; Nianhua Chen; Hui Yu; Xinyue Liu; Yujie Feng; Defeng Xing; Yushi Tian (Science of The Total Environment, 2024)

Sulfur cycle-mediated biological nitrogen removal and greenhouse gas abatement processes: Micro-oxygen regulation tells the story - Yu Zhang; Wei Wang; Xijun Xu; Quan Zhang; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Bioresource Technology, 2024)

Improved electrocatalytic activity and CO2 tolerance of iron-based perovskite as an intermediate temperature SOFC cathode - Yunlong Chen; Jiahui Zhu; Tifeng Xia; Yuqing Feng; Jiayi Chang; Xiaofei Zhu; Jinghe Bai; Jianqiu Wang; Wenfu Yan; Defeng Zhou (Fuel, 2024)

The generation and transformation mechanisms of reactive oxygen species in the environment and their implications for pollution control processes: A review - Zhihao Bi; Wei Wang; Lei Zhao; Xueting Wang; Defeng Xing; Yanfeng Zhou; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Environmental Research, 2024)

Genome and metabolome analysis of Bacillus sp. Hex-HIT36: A newly screened functional microorganism for the degradation of 1-hexadecene in industrial wastewater - Lei Yang; Chuan Chen; Xijun Xu; Xue-Ting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee (Environmental Research, 2024)

Enterobacter sp. HIT-SHJ4 isolated from wetland with carbon, nitrogen and sulfur co-metabolism and its implication for bioremediation - Kaili Fan; Fei Wang; Xijun Xu; Jia Shi; Wei Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Environmental Research, 2024)

Linking performance to dynamic migration of biofilm ecosystem reveals the role of voltage in the start-up of hybrid microbial electrolysis cell-anaerobic digestion - Xue-Ting Wang; Lei Zhao; Quan Zhang; Bo Wang; Defeng Xing; Jun Nan; Nan-Qi Ren; Duu-Jong Lee; Chuan Chen (Bioresource Technology, 2024)

Development of CadR-based cadmium whole cell biosensor for visual detection of environmental Cd2+ - Tianyi Zhang; KaiLi Zhu; Xia Zhang; Xin Yu; Liang Shen; Defeng Gao; Yiwen Chen; Qinghua Wang; Shaopeng Chen; Lingzhi Bao (Analytica Chimica Acta, 2024)

Editorial: Advances in autonomous ships (AS) for ocean observation - Xinyu Zhang; Yanlong Chen; Gorka Bidegain; Defeng Wu; Yanzhen Gu; Chengbo Wang (Frontiers in Marine Science, 2024)

Intensified partial nitrification and microbiome response in a membrane pulsing-aerated biofilm reactor - Zheng Zhong; Kun Feng; Yu Chen; Baiyun Lu; Jing Wang; Chuandong Wu; Defeng Xing (Chemical Engineering Journal, 2024)

Bonding characteristics between existing concrete substrate and high ductility geopolymer overlays under direct shear loading - Shan Li; Wentao Ma; Defeng Chen; Yiyan Lu; Zhenzhen Liu (Engineering Structures, 2024)

Efficient removal of hexavalent chromium from wastewater using a novel sodium alginate-biochar composite adsorbent - Yushi Tian; Xiaolin Sun; Nianhua Chen; Xintong Cui; Hui Yu; Yujie Feng; Defeng Xing; Weihua He (Journal of Water Process Engineering, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Mechanisms of metabolic regulation and enhanced methane production by hydrolytic nanozyme in sludge anaerobic digestion - Jing Wang; Cai Yan; Zheng Zhong; Baiyun Lu; Chuan Chen; Lei Zhao; Jun Ma; Defeng Xing (Chemical Engineering Journal, 2024)

Linking metabolomics to machine learning reveals the metabolic fates of the refractory industrial pollutant 1-Hexadecene - Lei Yang; Xijun Xu; Jin Yan; Wei Wang; Xueting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2024)

A high-performance composite cathode based on thermal expansion complementation for SOFC - Ling Hu; Defeng Zhou; Xiaofei Zhu; Ning Wang; Jinghe Bai; Huifang Gong; Youjie Zhang; Yunlong Chen; Wenfu Yan; Qiurong Zhu (Fuel, 2024)

A novel study of brain microvascular endothelial cells induced by astrocyte conditioned medium for constructing blood brain barrier model in vitro: A promising tool for meningitis of teleost - Yanghui Chen; Yuan Li; Junliang Luo; Zixin Li; Yu Huang; Jia Cai; Dongneng Jiang; Defeng Zhang; Jichang Jian; Jun Qiang; Bei Wang (Fish & Shellfish Immunology, 2024)

Recycling different crystal forms of MnO2 from spent Li-ion batteries cathodes for SDZ degradation - Xinxin Lv; Fang Deng; Huilai Liu; Yu Zhang; Qingjun Liu; Yueqing Liang; Defeng Kong; Mukhtar Ahmad; Xing Chen (Journal of Environmental Chemical Engineering, 2024)

Integrating network pharmacology and experimental validation to explore the mechanisms of luteolin in alleviating fumonisin B1–induced intestinal inflammatory injury - Defeng Wen; Wantong Han; Quan Chen; Guanhui Qi; Mengling Gao; Pu Guo; Yu Liu; Zhongyuan Wu; Shulin Fu; Qirong Lu; Yinsheng Qiu (Toxicon, 2024)

Investigation into the treatment and resource recovery of rifamycin mycelial dreg with thermal alkaline pretreatment-anaerobic digestion - Quan Zhang; Xuejiao Gong; Yu Zhang; Xueting Wang; Xiaowen Pan; Yanfeng Zhou; Xijun Xu; Qi Zhang; Xiao-Ming Ji; Weijun Wang; Defeng Xing; Nanqi Ren; et al. (Journal of Cleaner Production, 2023)

Mechanisms of magnetic sensing and regulating extracellular electron transfer of electroactive bacteria under magnetic fields - Huihui Zhou; Xianwen Xuanyuan; Xiaowei Lv; Jing Wang; Kun Feng; Chuan Chen; Jun Ma; Defeng Xing (Science of The Total Environment, 2023)

Carbon-based materials as highly efficient catalysts for the hydrogen evolution reaction in microbial electrolysis cells: Mechanisms, methods, and perspectives - Lina Xu; Wei Li; Jiaqin Luo; Lingyu Chen; Kuanchang He; Dongmei Ma; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Effects of long-term warming on soil prokaryotic communities in shrub and alpine meadows on the eastern edge of the Qinghai-Tibetan Plateau - Wei Li; Lingchen Yuan; Xianli Lan; Rui Shi; Dongdong Chen; Defeng Feng; Xinquan Zhao; Huai Chen (Applied Soil Ecology, 2023)

Co-treatment with free nitrous acid and calcium peroxide regulates microbiome and metabolic functions of acidogenesis and methanogenesis in sludge anaerobic digestion - Jing Wang; Yu Lou; Dongmei Ma; Kun Feng; Chuan Chen; Lei Zhao; Defeng Xing (Science of The Total Environment, 2023)

Conductive carrier promotes synchronous biofilm formation and granulation of anammox bacteria - Kun Feng; Yu Lou; Yitian Li; Baiyun Lu; Anran Fang; Guojun Xie; Chuan Chen; Defeng Xing (Journal of Hazardous Materials, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

A New Conditionally Immortalized Nile Tilapia (Oreochromis niloticus) Heart Cell Line: Establishment and Functional Characterization as a Promising Tool for Tilapia Myocarditis Studies - Yanghui Chen; Yuan Li; Dongneng Jiang; Defeng Zhang; Yu Huang; Jia Cai; Jichang Jian; Bei Wang (Fishes, 2023)
A new cell line named the tilapia heart cell line (TAH-11) was established from the heart of tilapia (Oreochromis niloticus) by enzymatic digestion and mechanical separation. The TAH-11 cell line has been stably subcultured for over 80 generations and resuscitated after being frozen in liquid nitrogen for six months, with exuberant cell growth. The optimal culture condition of TAH-11 is L-15 medium supplemented with 10% fetal bovine serum at 25 °C. Sequencing of the mitochondrial 18S rRNAs confirmed that TAH-11 cells were derived from the tilapia. TAH-11 was also identified as a myocardial cell line based on the mRNA expression of the troponin I, α-actin and myoglobin genes. Simultaneously, TAH-11 could be successfully transfected with the GFP reporter gene, suggesting that the TAH-11 cell line could be used for exogenous gene expression in vitro. The TAH-11 cells showed susceptibility to CGSIV, which was demonstrated by the presence of a severe cytopathic effect, suggesting that the TAH-11 cell line is an ideal tool for studying host–virus interaction and potential vaccines. In addition, the expression of inflammatory factors in TAH-11 cells can be remarkably induced following Streptococcus agalactiae or Streptococcus iniae. The present data lays a foundation to further explore the mechanism of how Streptococcus spp. causes tilapia myocarditis.

MSINGB: A Novel Computational Method Based on NGBoost for Identifying Microsatellite Instability Status from Tumor Mutation Annotation Data - Jinxiang Chen; Miao Wang; Defeng Zhao; Fuyi Li; Hao Wu; Quanzhong Liu; Shuqin Li (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

Falsigemmobacter faecalis gen. nov. sp. nov., isolated from faeces of Rhinopithecus roxellanae, and reclassification of Gemmobacter intermedius as Falsigemmobacter intermedius comb. nov - Guiding Li; Yi Jiang; Qinyuan Li; Xiu Chen; Longqian Jiang; Kun Zhang; Defeng An; Lei Lang; Li Han; Xueshi Huang; Chenglin Jiang (Archives of Microbiology, 2020)

Comparison of Anaerobic Methane Oxidation in Different Sediment Habitats of Dianchi Lake - Wei Li; Yue Chen; Mingmo Luo; Chunyan Li; Yonggui Zhao; Huai Chen; Defeng Feng; Bin Hu (Water, Air, & Soil Pollution, 2020)

Soil water content and pH drive archaeal distribution patterns in sediment and soils of water-level-fluctuating zones in the East Dongting Lake wetland, China - Wei Li; Defeng Feng; Gang Yang; Zhengmiao Deng; Junpeng Rui; Huai Chen (Environmental Science and Pollution Research, 2019)

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)

Root morphology in response to nitrogen supply in mid-season indica rice cultivars released in different decades - Yikai Zhang; Huizhe Chen; Yuping Zhang; Jing Xiang; Guangmei Ji; Defeng Zhu (Science China Life Sciences, 2017)

Dietary salt modulates the sodium chloride cotransporter expression likely through an aldosterone-mediated WNK4-ERK1/2 signaling pathway - Lingyun Lai; Xiuyan Feng; Defeng Liu; Jing Chen; Yiqian Zhang; Bowen Niu; Yong Gu; Hui Cai (Pflügers Archiv - European Journal of Physiology, 2012)